Aquatic Ecology : (Blackwell Science, 1994)
This volume comprises the proceedings of an International Symposium convened by the British Ecological Society and the American Society of Limnology and Oceanography. The contributors identify similarities and differences between freshwater and marine ecosystems, and examine the extent to which the scale of approach influences the patterns observed and the underlying processes implied.